Flow Cytometric Determination of Actin Polymerization in Peripheral Blood Leukocytes Effectively Discriminate Patients With Homozygous Mutation in ARPC1B From Asymptomatic Carriers and Normal Controls - Kopitar, Andreja N.; Markelj, Gašper; Oražem, Miha; Blazina, Štefan; Avčin, Tadej; Ihan, Alojz; Debeljak, Maruša (Frontiers in Immunology, 2019)
Actin nucleators initiate formation of actin filaments. Among them, the Arp2/3 complex has the ability to form branched actin networks. This complex is regulated by members of the Wiscott-Aldrich syndrome protein (WASp) family. Polymerization of actin filaments can be evaluated through flow cytometry by fluorescent phalloidin staining before and after stimulation with N-formyl-methionyl-leucyl-phenylalanine (fMLP). We identified a missense mutation in the gene ARPC1B (Arp2/3 activator subunit) resulting in defective actin polymerization in four patients (three of them were related). All patients (1 male, 3 female) developed microthrombocytopenia, cellular immune deficiency, eczema, various autoimmune manifestations, recurrent skin abscesses and elevated IgE antibodies. Besides four patients with homozygous mutation in ARPC1B, we also identified six heterozygous carriers without clinical disease (3 males, 3 females) within the same family. We developed a functional test to evaluate Arp2/3 complex function, which consists of flow cytometric detection of intracellular polymerized actin after in vitro fMLP stimulation of leukocytes. Median fluorescence intensities of FITC-phalloidin stained actin were measured in monocytes, neutrophils and lymphocytes of patients, carriers, and healthy control subjects. We detected non-efficient actin polymeristaion in monocytes and neutrophils of homozygous patients compared to carriers or the healthy subjects. In monocytes, the increase in median fluorescence intensities was significantly lower in patients compared to carriers (104% vs 213%; p<0.01) and healthy controls (104% vs. 289%; p<0.01). Similarly, the increase in median fluorescence intensities in neutrophils was significantly increased in the group with carriers (208%; p<0.01) and healthy controls (238%; p<0.01) and significantly decreased in the patient's group (94%). Our functional fMLP/phalloidin test can therefore be used to efficiently discriminate homozygous symptomatic patients from asymptomatic heterozygous carriers.